2018
DOI: 10.1155/2018/6821601
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Differentiation-3 and Estrogenic Endocrine Disruptors: Implications for Susceptibility to Obesity and Metabolic Disorders

Abstract: The rising global incidence of obesity cannot be fully explained within the context of traditional risk factors such as an unhealthy diet, physical inactivity, aging, or genetics. Adipose tissue is an endocrine as well as a metabolic organ that may be susceptible to disruption by environmental estrogenic chemicals. Since some of the endocrine disruptors are lipophilic chemicals with long half-lives, they tend to bioaccumulate in the adipose tissue of exposed populations. Elevated exposure to these chemicals ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 146 publications
0
16
0
Order By: Relevance
“…As one of Inhibitor of DNA binding family, ID3 have been known to regulate cell growth, self‐renewal, senescence, angiogenesis, and neurogenesis (Doke, Avecilla, & Felty, ). The ID3 is biologically relevant to neurological and behavior research because of its involvement in the stress response, neural plasticity, and neural circuitry (Avecilla, Doke, & Felty, ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of Inhibitor of DNA binding family, ID3 have been known to regulate cell growth, self‐renewal, senescence, angiogenesis, and neurogenesis (Doke, Avecilla, & Felty, ). The ID3 is biologically relevant to neurological and behavior research because of its involvement in the stress response, neural plasticity, and neural circuitry (Avecilla, Doke, & Felty, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further roles of endocrine disruption have been found in relation to metabolic disorders, including alteration of cholesterol metabolism, weight gain, obesity [56][57][58] and type 1 and 2 diabetes [22,59].…”
Section: Endocrine Disruptors and Human Healthmentioning
confidence: 99%
“…The members of the ID family share an extensive amino acid sequence homology within their HLH (helix-loop-helix) domain (69–78%) [ 17 , 18 ]. It has been reported that ID protein acts as a transcription regulator, which regulate the transcription in a dominant-negative manner by dimerizing with basic HLH transcription factors like HEB, E47, and E12 [ 19 , 20 , 21 ]. ID proteins are pleiotropic proteins involved in the modulation of biological processes, such as cell proliferation and differentiation, cell cycle control, senescence, apoptosis or angiogenesis, and metastasis [ 22 , 23 ].…”
Section: Inhibitor Of Differentiationmentioning
confidence: 99%